Correlation between personality types and english proficiency among the students of Didactica III in their 6th semester of academic year 2012 of the Licenciatura en Idioma Inglés opción Enseñanza, at Universidad de El Salvador - Osorio Naves, Mariel Ismenia
This study shows the correlation between personality types and English proficiency levels from a sample group currently taking Didáctica III in their 6th semester of the Licenciatura en Idioma Ingles Opción Enseñanza, at the Foreign Language Department at Universidad de El Salvador. To carry out this study, the researchers utilized a survey, which asked students about their general information; a predesigned personality test, to determine students’ personality types; and a standardized proficiency test (paper based TOEFL practice test) to discover students’ proficiency level. The data collected was analyzed descriptively for most variables and a correlational study was carried out between personality types and their respective proficiency levels using statistical correspondence analysis. The sample chosen did not yield any individuals that could be placed in the highest or lowest proficiency levels in the CEF scale, and did not provide the expected 16 personality types. Though 13 different personalities were found among the students in the sample, most of them were underrepresented with only 2 or 3 students from the sample; therefore, to carry out the correlational study 4 predominant personality types were used, which represents 61% of the individuals in the sample. This study did show a correlation between students’ personality types and their English proficiency level, though the lack of subjects in the highest and lowest proficiency levels made it impossible to determine a specific personality type related to greater success or failure.